The association between living alone and depressive symptoms in older adults population: evidence from the China Health and Retirement Longitudinal Study - Hui Fang; Yingxin Duan; Yinxin Hou; Haoran Chang; Shanju Hu; Ruyi Huang; Ruyi Huang (Frontiers Media S.A., 2024)
ObjectiveThe goal of this research was to reveal the association between living alone and depressive symptoms in older adults. It also aims to explore the mediating role of social activity and adult children's relationship satisfaction. Ultimately, the study seeks to add to the body of knowledge for lowering the risk of depression among older people and promoting positive aging.MethodsBased on information from the 2020 China Health and Retirement Longitudinal Study, the ordinary least square (OLS) regression model and propensity score matching (PSM) were used to investigate the association between living alone and depressive symptoms in older adults and to explore possible heterogeneity in different groups. Utilizing the SPSS PROCESS macro application, the mediation model was constructed. The significance of the mediation effect was investigated using the Bootstrap technique.ResultsThe average level of depressive symptoms of older people living alone (10.55 ± 6.962) was higher than that of older people who do not live alone (8.80 ± 6.363). The baseline regression analysis revealed a significant connection between living alone and the depressive symptoms of older people (β = 0.842, p < 0.001). The association between living alone and the level of depressive symptoms was significantly higher in those aged 60-74 years (β = 1.698, p < 0.001) than in those aged 75 and older (β = 0.953, p < 0.05). The association between living alone and depressive symptoms was significantly higher in rural older adults (β = 1.512, p < 0.001) than in urban older adults (β = 1.141, p < 0.001). Between living alone and the level of depressive symptoms experienced by older people, there was a substantial mediation impact on social engagement and adult children's relationship satisfaction, which contributed to 2.91 and 13.62% of the overall effect.ConclusionFor older age groups, living alone is associated with higher levels of depressive symptoms. This effect is stronger in older adults aged 60-74 or rural areas. In older age groups, the association between living alone and depressive symptoms is mediated by social activity and adult children's relationship satisfaction.